(untitled) (Journal of responsible AI & ethics, 2026)
The integration of Artificial Intelligence (AI) into healthcare has the potential to revolutionize patient care by improving diagnostic accuracy, optimizing treatment plans, and enhancing operational efficiency. However, the application of AI in healthcare also raises critical ethical and responsibility concerns. AI systems in healthcare must be designed and deployed in a manner that ensures patient privacy, equitable care, transparency, and accountability. This paper explores the ethical implications of AI in healthcare, examining issues such as data privacy, algorithmic biases, autonomy, and informed consent. By reviewing case studies, current AI applications, and theoretical frameworks, this paper investigates how AI can be implemented in a manner that prioritizes patient welfare and ethical practices. The study concludes with recommendations for developing ethical AI standards in healthcare and strategies for minimizing risks such as discrimination and lack of transparency. The findings underscore the importance of collaboration between healthcare professionals, AI developers, and regulatory bodies to ensure that AI technologies are used responsibly and equitably to benefit all patients.